Evolutionary model of folk economics: That which is seen, and that which is not seen?. (30th August 2018) - Stastny, Dan; Houdek, Petr
Abstract: Although Boyer & Petersen (B&P) make the case for evolutionary roots of folk economics stronger, their evolutionary model ultimately does not deliver folk-economic explanations that are both novel and correct. We argue that (a) most current explanations are evolutionary already; (b) B&P's model is as ad hoc as other theories, and proves too much; and (c) it overrates evolution at the cost of discounting other crucial factors.